(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
Chronic hepatitis remains one of the most pressing issues in modern hepatology, and the role of metabolic factors in its development and progression has been steadily increasing. Epidemiological and clinical studies conducted in recent years indicate that insulin resistance represents an important pathogenetic factor in the development of liver diseases. Disruption of insulin signaling leads to impaired lipid metabolism in hepatocytes, increased triglyceride accumulation, and activation of oxidative stress. These processes promote the production of inflammatory mediators and contribute to the development of hepatic fibrosis. According to data reported in the scientific literature, patients with insulin resistance have a significantly higher risk of developing liver fibrosis, which in turn increases the likelihood of progression to severe forms of chronic hepatitis. This article analyzes the molecular mechanisms, epidemiological aspects, and clinical significance of insulin resistance in the pathogenesis of chronic hepatitis based on contemporary scientific literature.